2008
DOI: 10.1002/asl.180
|View full text |Cite
|
Sign up to set email alerts
|

Error‐correction methods and evaluation of an ensemble based hydrological forecasting system for the Upper Danube catchment

Abstract: Within the EU Project PREVention, Information and Early Warning (PREVIEW), ensembles of discharge series have been generated for the Danube catchment by the use of various weather forecast products. Hydrological models applied for streamflow prediction often have simulation errors that degrade forecast quality and limit the operational usefulness of the forecasts. Therefore, error-correction methods have been tested for adjusting the ensemble traces using a transformation derived with simulated and observed fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 28 publications
1
39
0
Order By: Relevance
“…Recent research results from HEPEX are encouraging and demonstrate the potential benefit of probabilistic weather forecasts over deterministic ones for flood forecasting in large river basins Buizza, 2008;Bogner and Kalas, 2008;Gebhardt et al, 2008;Marty et al, 2008;Pappenberger et al, 2008b;Schalk et al, 2008;Tucci et al, 2008;Zappa et al, 2008). Roulin (2007) demonstrated that EPS-based flood forecasting can also be valuable for small river basins, while advances in limited area EPS modelling may provide even better quantitative precipitation estimates also for small basins (Marsigli et al, 2001;Marsigli et al, 2005;Tibaldi et al, 2006).…”
Section: J Thielen Et Al: Efas -Concept and Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research results from HEPEX are encouraging and demonstrate the potential benefit of probabilistic weather forecasts over deterministic ones for flood forecasting in large river basins Buizza, 2008;Bogner and Kalas, 2008;Gebhardt et al, 2008;Marty et al, 2008;Pappenberger et al, 2008b;Schalk et al, 2008;Tucci et al, 2008;Zappa et al, 2008). Roulin (2007) demonstrated that EPS-based flood forecasting can also be valuable for small river basins, while advances in limited area EPS modelling may provide even better quantitative precipitation estimates also for small basins (Marsigli et al, 2001;Marsigli et al, 2005;Tibaldi et al, 2006).…”
Section: J Thielen Et Al: Efas -Concept and Developmentmentioning
confidence: 99%
“…A detail case study of the EFAS performance during the spring floods in 2006 in Slovakia, for the Morava River (tributary to the Danube), has been recently published by Kalas et al (2008), and a case study on the performance of the system during the Elbe floods by . For the 2002 Danube floods, EFAS re-forecasts were produced and Bogner and Kalas (2008) have been looking into novel post-processing methods to remove forecast biases in the outputs and thus produce more reliable results with a reduced, but more meaningful, spread. The analysis of the EFAS performance during the flood events in Romania from 22-25th October 2007 has been recently finalized (Thielen et al, submitted).…”
Section: × ×mentioning
confidence: 99%
See 1 more Smart Citation
“…In the work of Bogner and Kalas [16], an error-correcting method was developed combining wavelet transformations (e.g., Beylkin and Saito [17], Chou and Wang [18]) and Vector AutoRegressive Models with eXogeneousinput (Wave-VARX). The idea was to incorporate not only the most recent information of the error in the correction model, but also information with time lags of several hours and days.…”
Section: Error Correctionmentioning
confidence: 99%
“…This is relatively easy to implement but neither represents the physical processes nor updates the ''memory'' associated with state variables such as soil moisture storages. Various error correction approaches, including artificial neural network (ANN) models [Anctil et al, 2003;Shamseldin and O'Connor, 2001], parametric simple linear (PSL) models [Goswami et al, 2005], autoregressive moving average (ARMA) models [Broersen, 2007], and ARMA with exogenous input (ARMAX) models [Bogner and Kalas, 2008], have been used to update predicted discharge. State and parameter updating schemes are more popular approaches as they attribute the error in predicted discharge to individual components within the rainfall-runoff process, which is more process based, and the uncertainty reduction in states and parameters is more beneficial for forecasting purposes.…”
Section: Introductionmentioning
confidence: 99%